Unraveling the role of introduced W in oxidation tolerance for Pt-based catalysts via on-line inductive coupled plasma-mass spectrometry - Han, Man Ho; Ko, Young Jin; Min, Byoung Koun; Yu, Seung-Ho; Choi, Chang Hyuck; Choi, Jae-Young; Lee, Woong Hee; Oh, Hyung-Suk (Elsevier BV, 2022)
Water electrolysis cells and fuel cells have attracted considerable attention because they provide renewable and sustainable energy conversion and storage systems. Pt is the best catalyst for these two devices. However, cathodic Pt dissolution can occur after the oxidation of Pt, degrading the Pt catalyst. We report a PtW/C catalyst with high oxidation tolerance under repeated reverse-potential tests. The prepared PtW/C catalyst possesses higher oxidation tolerance than does the commercial Pt/C catalyst under repeated reverse-potential tests while showing comparable catalytic activity. From a combination of on-line inductively coupled plasma-mass spectrometry (ICP-MS) and ex-situ spectroscopy, we suggest that cathodic Pt dissolution is significantly inhibited because the introduced W suppresses the oxidation of Pt in PtW/C. However, W is dissolved in PtW/C rather than in Pt, indicating the need for further research. Our study demonstrates a new perspective for developing Pt-based catalysts with high oxidation tolerance by reducing cathodic Pt dissolution.